2015
DOI: 10.1371/journal.pone.0136080
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistance-Associated Protein 2 Expression Is Upregulated by Adenosine 5’-Triphosphate in Colorectal Cancer Cells and Enhances Their Survival to Chemotherapeutic Drugs

Abstract: Extracellular adenosine 5’-triphosphate (ATP) is a signaling molecule that induces a plethora of effects ranging from the regulation of cell proliferation to modulation of cancerous cell behavior. In colorectal cancer, ATP was reported to stimulate epithelial cell proliferation and possibly promote resistance to anti-cancer treatments. However, the exact role of this danger-signaling molecule on cancerous intestinal epithelial cells (IECs) in response to chemotherapeutic agents remains unknown. To address how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“…In addition, ATP at a very high dose in the range of milli molar was reported to induce cytotoxicity and apoptosis in many cancer types such as hepatoma, adenocarcinoma, and cervical cancer cells (24,(30)(31)(32)(33). On the other hand, some studies have showed that 10 μM ATP and lower doses stimulated growth and motility of ovarian cancer (34), hepatoma (19), breast cancer (23), lung cancer (25), and prostate cancer cells (20,35). To utilize ATP and/or adenosine in vivo, one must consider the final dose of the compounds at the tumor sites.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ATP at a very high dose in the range of milli molar was reported to induce cytotoxicity and apoptosis in many cancer types such as hepatoma, adenocarcinoma, and cervical cancer cells (24,(30)(31)(32)(33). On the other hand, some studies have showed that 10 μM ATP and lower doses stimulated growth and motility of ovarian cancer (34), hepatoma (19), breast cancer (23), lung cancer (25), and prostate cancer cells (20,35). To utilize ATP and/or adenosine in vivo, one must consider the final dose of the compounds at the tumor sites.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was isolated from the liver of 12-week-old mice using the ToTALLY RNA Total RNA Isolation Kit (Thermo Fisher Scientific) and RNA purified Qiagen RNeasy minikit (Qiagen, Toronto, ON). Complementary DNA was synthesized from 2 μg of purified RNA as previously described 63 . Quantitative real-time PCR analyses were realized as previously reported 63 using the mouse sequence-specific primers for Acaca : 5′-GATGAACCATCTCCGTTGCG-3′ and 5′-GAGCCAATTATGAATCG GGACTG-3′, Acacb : 5′-TTCCCCAGCCAGCAGATAGC-3′ and 5′-CTTCATGTAGCCACGGGTCC-3′, Fasn : 5′-GATGAAGAGGGACCATAAAGAATAA-3′ and 5′-GCACTTGATGTGAG GGGAGAT3′, Acox1 : 5′-CCGCCACCTTCAATCCAGAG-3′ and 5′-CAAGTTCTCGATTTCTCGACGG-3′, and Mlxipl : 5′-CTGGGGACCTAAACAGGAGC-3′ and 55′-GAAGCCACCCTATAGCTCCC-3′.…”
Section: Methodsmentioning
confidence: 99%
“…Complementary DNA was synthesized from 2 μg of purified RNA as previously described 63 . Quantitative real-time PCR analyses were realized as previously reported 63 using the mouse sequence-specific primers for Acaca : 5′-GATGAACCATCTCCGTTGCG-3′ and 5′-GAGCCAATTATGAATCG GGACTG-3′, Acacb : 5′-TTCCCCAGCCAGCAGATAGC-3′ and 5′-CTTCATGTAGCCACGGGTCC-3′, Fasn : 5′-GATGAAGAGGGACCATAAAGAATAA-3′ and 5′-GCACTTGATGTGAG GGGAGAT3′, Acox1 : 5′-CCGCCACCTTCAATCCAGAG-3′ and 5′-CAAGTTCTCGATTTCTCGACGG-3′, and Mlxipl : 5′-CTGGGGACCTAAACAGGAGC-3′ and 55′-GAAGCCACCCTATAGCTCCC-3′. Gene expression was normalized to Tbp gene expression as previously reported 64 .…”
Section: Methodsmentioning
confidence: 99%
“…Purinergic signaling has been known to promote cell growth and proliferation [182,183] . Purinergic receptors such as members of the P2X and P2Y families were reported to be involved in cancer drug resistance [184][185][186] . In one recent study, researchers demonstrated that ATP promoted resistance to chemotherapeutic drugs in colorectal cancer cells through P2Y-mediated upregulation of MRP2 and concurrent drug pumping [187] .…”
Section: Atp and Atp-mediated Drug Resistancementioning
confidence: 99%